Pembiasaan Kegiatan Literasi Sebagai Fasilitas Peserta Didik Yang Belum Lancar Membaca Di Sekolah Dasar - Hidayat, Nashruddin; Widyasari, Choiriyah (Cetta: Jurnal Ilmu Pendidikan, 2025)
This study aims to describe the implementation of literacy activity habits as a facility for students who are not yet fluent in reading. The focus of the study was to explore the methods used by the school in the habit of literacy activities for students who are not yet fluent in reading, and to identify factors that influence the smoothness and obstacles to the implementation of reading literacy activities. The method used was descriptive qualitative with data collection techniques through observation, interviews and documentation. The subjects of the study consisted of the principal, teachers, curriculum vice principal, students. The results of the study showed that MI Muhammadiyah Gayam had implemented literacy activity habits as a facility for students who were not yet fluent in reading, before learning students were given 10-15 minutes to read. Supporting factors in the implementation of this literacy activity habit provide reading assistance to students who still have difficulties which is carried out intensively, while inhibiting factors include the unavailability of a library, limited reading materials, lack of comfortable reading rooms, and low levels of parental involvement in supporting children's reading habits at home. Teachers' efforts to overcome obstacles by providing a reading corner in each class and reading books and teachers working together with parents in supporting students' habit of reading every day.